Penegakan Hukum Terhadap Anak Yang Melakukan Tindak Pidana Kefarmasian (Study Kasus Putusan No. 252/PID.SUS/ANAK/2013/PN.KDI) - Ida Bagus Putra Mahardika; I Made Minggu Widyantara; I Ketut Sukadana (Jurnal Analogi Hukum, 2019)
The drug benefit as basically has disappeared or pain can heal. Rampant circulation of drugs without a permission path in society concern as members of the community, as opposed to law No. 36 year 2009 about health. In the violation is not only done by adults and institutions or companies, but it has been done by children under. As for the formulation of the problem (1) How pharmacy settings according to positive law in Indonesia? (2) How sanctions against children who commit criminal acts of Pharmacy? Researchers using normative and the method research approach and a conceptual approach to legislation. Pharmacy settings according to positive law in Indonesia is regulated in Act No. 36 of the year 2009 on health, with criminal provisions set forth in Chapter XX, namely Article 190 to article 201. The application of sanctions on children who commit criminal acts Pharmacy with criminal threats maximum 15 (fifteen) years and a fine of maximum RP 1.5 billion (one billion five hundred million rupiah) cannot be processed through appropriate breathtaking diversion provisions Article 7 paragraph (2) of the law number 11 year 2012 about the criminal justice system.